Synthesis of new halogenated compounds based on 8-hydroxyquinoline derivatives for the inhibition of acid corrosion: Theoretical and experimental investigations. (December 2022) - Rbaa, M.; Galai, M.; Ouakki, M.; Hsissou, R.; Berisha, A.; Kaya, Savaş; Berdimurodov, Elyor; Lakhrissi, B.; Zarrouk, A.
Abstract: In the present work, a new 8-hydroxyquinoline substituted with bromine (Q-C4Br) and chlorine (Q-C4Cl) was first synthesized and introduced as a powerful corrosion inhibitor for carbon steel in 1.0 M HCl. These compounds were obtained in high yield, and their structures were characterized by infrared (IR) spectroscopy, NMR spectroscopy ( 13 C, 1 H) and elemental analysis (EA). The anti-corrosion properties of Q-C4Br and Q-C4Cl were tested by experimental [mass loss (ML), potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS)] and theoretical [density functional theory (DFT), Monte Carlo simulations (MC) and molecular dynamic simulations (MD] methods. Inductively coupled plasma mass spectrometry-optical emission spectrometry (ICP-OES) and UV–visible spectroscopy (UV–vis) were used to identify the corrosion and inhibition processes in solutions. The surface morphology of the steel surface after corrosion and inhibition processes was investigated by AFM, EDS, SEM and FT-IR spectroscopy. It is found that these compounds are ideal corrosion inhibitors for steel, and Q-C4Cl was a better inhibitor than Q-C4Br. The inhibition behavior, chelation characteristics, donor-acceptor effects and coordination bonding properties of the 8-hydroxyquinoline ring were enhanced by the Br and Cl modifications. The obtained results may be useful for creating the next generation of corrosion inhibitors based on aromatic compounds in future research works. Graphical Abstract: ga1